2002
DOI: 10.4049/jimmunol.169.8.4147
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Cyclic Adenosine 5′-Monophosphate Response Element Modulator Up-Regulates IL-2 in T Cells from Patients with Systemic Lupus Erythematosus

Abstract: The cAMP response element modulator (CREM) has been shown to bind specifically to the −180 site of the IL-2 promoter in vitro. CREM protein is increased in T cells of patients with systemic lupus erythematosus (SLE), and it has been considered responsible for the decreased production of IL-2. In this work we show that transcriptional up-regulation is responsible for the increased CREM protein levels and that CREM binds to the IL-2 promoter in live SLE T cells. Suppression of the expression of CREM mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 37 publications
2
72
0
1
Order By: Relevance
“…Previous work from this laboratory has established that decreased IL-2 production by human SLE T cells is the consequence of defective IL-2 gene transcription caused by increased expression of the repressor CREM (6,8). This finding instigated experiments reported herein to understand what causes the up-regulation of CREM in T cells and how CREM suppresses IL-2 production.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous work from this laboratory has established that decreased IL-2 production by human SLE T cells is the consequence of defective IL-2 gene transcription caused by increased expression of the repressor CREM (6,8). This finding instigated experiments reported herein to understand what causes the up-regulation of CREM in T cells and how CREM suppresses IL-2 production.…”
Section: Discussionmentioning
confidence: 91%
“…An empty vector plasmid (PGS5) served as control. We have previously reported that the activity of a luciferase reporter construct driven by the IL-2 promoter is reduced by a CREM ␣ plasmid while enhanced by an antisense plasmid in T cells (8). In Fig.…”
Section: Antisense Crem ␣ Treatment Inhibits the Binding Of Crem To Tmentioning
confidence: 99%
“…Investigators at our laboratory have demonstrated that reconstitution of p65 NF-B restores CD3-mediated IL-2 production in SLE T cells (11), as does the elimination of the transcription repressor CREM using an antisense CREM plasmid (18). In those approaches, though, a suboptimal dose of phytohemagglutinin A was used to condition the cells for gene transfer, and this process may have altered cell physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Because regulation of the production of IL-2 is complex, and in patients with SLE the decreased production is the result of increased expression of the transcriptional repressor cAMP response element modulator (33,34), it is possible that increased production of IL-2 occurs at the ignition of the autoimmune response.…”
Section: Discussionmentioning
confidence: 99%